A geospatial web-based integrative analytical tool for the water-energy-food nexus: the iWEF 1.0 - Taguta, C.; Nhamo, L.; Kiala, Zolo; Bangira, T.; Dirwai, Tinashe Lindel; Senzanje, A.; Makurira, H.; Jewitt, G.P.W.; Mpandeli, S.; Mabhaudhi, Tafadzwanashe (Frontiers Media, 2023)
Introduction: The water-energy-food (WEF) nexus has evolved into an important transformative approach for facilitating the timely identification of trade-offs and synergies between interlinked sectors for informed intervention and decision-making. However, there is a growing need for a WEF nexus tool to support decision-making on integrated resources management toward sustainable development. Methods: This study developed a geospatial web-based integrative analytical tool for the WEF nexus (the iWEF) to support integrated assessment of WEF resources to support resilience building and adaptation initiatives and strategies. The tool uses the Analytic Hierarchy Process (AHP) to establish numerical correlations among WEF nexus indicators and pillars, mainly availability, productivity, accessibility, and sufficiency. The tool was calibrated and validated with existing tools and data at varying spatio-temporal scales. Results: The results indicate the applicability of the tool at any spatial scale, highlighting the moderate sustainability in the management of WEF resources at various scales. The developed iWEF tool has improved the existing integrative WEF nexus analytical tool in terms of processing time and providing geospatial capabilities. Discussion: The iWEF tool is a digital platform that automatically guides policy and decision-making in managing risk from trade-offs and enhancing synergies holistically. It is developed to support policy and decision-making on timely interventions in priority areas that could be showing signs of stress.